Internal Orifice Alloy Closure—A New Procedure to Treat Anal Fistula - Li, Ming; Fang, Xiaoli; Zhang, Jun; Deng, Heng (Frontiers in Surgery, 2022)
Background The internal orifice plays an important role in pathogenesis and treatment of most complex fistula-in-ano. The treatment of the internal orifice is considered to be the key to the success of anal fistula surgery. The objective of this study was to evaluate the feasibility of a new sphincter-sparing surgical approach for anal fistula. Materials and Methods All hospitalized anal fistula patients were included in this study. Preoperative anorectal ultrasound was done in all the patients. Transanal internal orifice alloy closure (IOAC) was performed through disposable titanium nickel alloy anal fistula stapler. The external sphincter was not cut. Anal fistula brush was used to curette and clean fistulas. Postoperative anorectal color ultrasound was used for evaluation at 2 months postoperatively. RESULTS 21 patients with fistula-in-ano were included (follow-up:6-11 months). Male/Female:18/3, age-39.7 ±10.5 years. 38.1%(8) had multiple tracts, 9.5%(2) belonged to high anal fistula. 23.8%(5) of anal fistula patients were complicated with Crohn's disease. Fistula healed completely in 85.7%(18/21) and didn’t heal in 14.3%(3/21). 3 patients who did not heal were re-performed with conventional surgery and eventually healed. Except for 3 patients undergoing additional traditional anal fistula surgery, the Wexner Incontinence scores of other patients did not change after surgery compared with before surgery. CONCLUSIONS IOAC is a novel sphincter-saving technique that is simple effective to treat anal fistula containing crohn's anal fistula.